Aplikasi Pupuk Hayati Illetrisoy pada Tanaman Kedelai dan Pengaruhnya terhadap Populasi Mikroba Tanah - Prihastuti Prihastuti (Sains dan Matematika, 2013)
Illetrisoy is a biological fertilizer for soybeans, improvised by Indonesian Legume and Tuber Crops Research Institute, consisting in two forms of formulations A and B. This study aimed to determine the benefits of Illetrisoy bio-fertilizer application on growth and seed yield, as well as its effect on soil microbial populations.ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ ï¿½ The research was conducted at the Indonesian Legume and Tuber Crops Research Institute, using of biological fertilizers Illetrisoy and soybean Grobogan variety. Design of the experiment used was a factorial randomized block with six replications. The first factor was the manure application consists of (1) without any manure, and (2) given manure. The second factor is giving inoculant Illetrisoy, consisting of (1) without inoculant, given inorganic fertilizer P, K, (2) without inoculant, given inorganic fertilizer N, P and K, (3) inoculation Illetrisoy A, and (4) inoculation Illetrisoy B. The results showed that the application of bio-fertilizers Illetrisoy on soybean has not significant effect on the physical variability of plants 45 days after planting and seed yield, compared to the treatment of manure and NPK application. The highest seed yields achieved on the application of Illetrisoy B accompanied with the application of manure and NPK fertilizer reached 50% (19.20 g seed/plant), which is not significantly different from the standard cultivation with application of NPK fertilizers which reached 18.43 g seed / plant. The analysis of the soil before and after soybeans planted, showed an improvement of chemically and biologically soil properties in terms of nutrient content (especially N and K) and total soil microbial population up to a hundred times.